An Efficient Inventory Rationing Strategy for Systems with Two Demand Classes and Backordering - Liu, S.; Zhang, Changyong (Taylor & Francis, 2015)
For systems with two customer classes and backordering, the formulae for the optimal dynamic critical levels in the literature are too complex to be extended to large values of critical levels. In this paper, an efficient method is introduced to obtain approximate closed-form expressions for the dynamic critical levels, even for large values. It is further verified by numerical results the accuracy of the approximate expressions, from which important managerial insights can be obtained.